(untitled) (Swiss Medical Weekly, 2025)
STUDY AIMS: Although surgeons face ethical questions and conflicts in daily practice, surgical education lacks ethics training. This study explores the relevance of clinical ethics consultations in addressing ethical conflicts and their potential role in surgical education. METHODS: This study explored the role of clinical ethics consultations (CECs) between 2012 and 2021 in both formal and informal surgical ethics education. First, data from each clinical ethics consultation were retrieved from the electronic medical database of the clinical ethics consultation services of the University Hospital Basel (USB) and the University Psychiatric Clinics Basel (UPK). Second, the data were analysed using thematic and contextual analysis. In the final step, the analysis included the identification of the educational focus. The methodological approach aimed to provide a detailed exploration of the role of clinical ethics consultations in surgical ethics education, despite the inherent constraints associated with document analysis and practical limitations regarding participant observation and interviewing. RESULTS: Of the 359 clinical ethics consultations examined, 38 were related to surgical interventions and conditions. Surgeons were involved in all 38 clinical ethics consultations, but surgical residents were involved in only 17 (45%), including 10 (26%) that they had requested themselves. These 17 clinical ethics consultations met the inclusion criteria and were suitable for in-depth analysis. Analysis of the ethical topics (maximum of three per case) revealed four main themes: patients’ wishes (n = 8), treatment planning (n = 5), treatment of somatic diseases in patients with additional mental disorders (n = 5), and challenges in dealing with patients’ representatives/relatives (n = 4). CONCLUSIONS: Ethical issues faced by surgical residents are often unrelated to primary surgical concerns. Despite the importance of ethical decision-making training in medical education, residents participated in less than half of clinical ethics consultations. Surgical faculty should involve residents in interdisciplinary discussions and clinical ethics consultations to increase awareness. Surgical curricula should incorporate resources to improve ethics-related decision-making skills.